A comprehensive study of terrain‐disrupted airflow at Hong Kong International Airport – observations and numerical simulations. (8th October 2019) - Chan, P.W.; Hon, K.K.; Li, Q.S.
Abstract : Complex terrain near the Hong Kong International Airport (HKIA) is likely to bring about low‐level windshear and turbulence to the aircraft, which could result in aviation hazards. In the past, some isolated case studies have been presented on the complicated airflow at the airport region in Hong Kong. This paper presents a more comprehensive discussion of the terrain‐induced airflow disturbances at the HKIA, including extensive mountain wake, transient low‐level jet stream, elongated mountain wake, reverse flow and mountain wave. The performance of a super high‐resolution numerical weather prediction model in the forecasting of these weather phenomena is also discussed. The model turns out to be capable of forecasting most of the terrain‐disrupted airflow, and it may be possible to obtain an earlier indication of the occurrence of low‐level windshear for airports with complex terrain. However, some mesoscale weather phenomena, such as low‐level jet stream, may not be captured by the models, and the associated windshear events would be difficult to forecast. This paper could hopefully be a useful reference to the aviation weather forecasters in the prediction of wind and windshear at airports with similar complex terrain in other parts of the world. Abstract : A simulated Light Detection And Ranging (LiDAR) picture (upper) with the vertical cross‐section (eastern side of the upper panel) of vertical velocity (lower), showing a mountain wave near the airport.